Contextual-Based Qiroatul Kutub Learning Using The Plickers - Zubaidi, Ahmad; Adawiyah, Siti Afifah; Syamsiyah, Dailatus; Zunairoh, Yuyun (Universitas Islam Negeri Raden Intan Lampung, 2022)
During the past decades, Qiroatul Kutub has been adopted as the learning model, therefore, this study is aimed to explore the development of the Qiroatul Kutub model using the Plickers application and the feasibility of it. Driven by Borg and Galls model of research and development (RnD), the researchers collected the data through documentation of 35 University students including expert assessments of learning method, materials and media. The expert validity test is based on 3 aspects of the module, learning model, and learning media using five scale analysis techniques, namely very good to very poor. From the expert validity test, an average score of 3.7 (A) was obtained, which was very good in terms of modules, learning models, and learning media, while the limited test to 32 student respondents obtained 3.8 (A) or very well from 3 aspects. Then after the revision, field testing was carried out and got an average score of 4 (A) or very good with an increase in student achievement from the pre-test and post-test results of 19.15%, indicating that the development of this learning model is very feasible to use. Drawing on the findings, this study provided an insightful finding on the adoption of Plickers application in Arabic reading skills. Thus, the teacher could incorporate this application to gain better students reading skills.